Immunogenic recombinant Burkholderia pseudomallei MprA serine protease elicits protective immunity in mice - Chin, Chui-Yoke; Tan, Swee-Chen; Nathan, Sheila (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia pseudomallei is resistant to a diverse group of antimicrobials including third generation cephalosporins whilst quinolones and aminoglycosides have no reliable effect. As therapeutic options are limited, development of more effective forms of immunotherapy is vital to avoid a fatal outcome. In an earlier study, we reported on the B. pseudomallei serine MprA protease, which is relatively stable over a wide pH and temperature range and digests physiological proteins. The present study was carried out to evaluate the immunogenicity and protective efficacy of the MprA as a potential vaccine candidate. In BALB/c mice immunized with recombinant MprA protease (smBpF4), a significantly high IgG titer was detectable. Isotyping studies revealed that the smBpF4-specific antibodies produced were predominantly IgG1, proposing that immunization with smBpF4 triggered a Th2 immune response. Mice were immunized with smBpF4 and subsequently challenged with B. pseudomallei via the intraperitoneal route. Whilst control mice succumbed to the infection by day 9, smBpF4-immunized mice were protected against the lethal challenge and survived beyond 25 days post-infection. In conclusion, MprA is immunogenic in melioidosis patients whilst also eliciting a strong immune response upon bacterial challenge in mice and presents itself as a potential vaccine candidate for the treatment of melioidosis.